A Content Analysis of Extension’s Presence on 1890 Land-Grant University Websites - Garrett M Steede; Laura Fischer; Diane C Meyer; Courtney Meyers (Journal of Applied Communications, 2018)
The 1890s land-grant university was established to provide the tripartite mission of education, outreach, and research to rural and urban audiences. However, it is challenging to complete this mission if the Extension aspect of an 1890 university is not easily found through online media. The purpose of this study was to evaluate the online presence and technology presence of 1890 land-grant Extension programs on their respective university and college (or equivalent) websites. This content analysis of 18 land-grant universities found only one university had a direct click from the university homepage to the Extension homepage while 10 of the 19 schools had a direct click from the college (or equivalent) webpage to the Extension homepage. Additionally, Extension was not found to be promoted on the majority of university homepages. Twelve Extension programs were featured on the college (or equivalent) website. Using the DAGMAR model, it was concluded that the public’s awareness of Extension is limited if the programs are not readily accessible to the target population from university websites. The researchers recommend university communication specialists strive to promote Extension on homepages and through social media. Future research should include analyzing the social media content these Extension programs provided and evaluating each institution’s Extension website for usability.
Keywords: online presence; 1890 land-grant university; Extension; website